Design, Synthesis, Chemical and Biochemical Insights Into Novel Hybrid Spirooxindole-Based p53-MDM2 Inhibitors With Potential Bcl2 Signaling Attenuation - Aziz, Yasmine M. Abdel; Lotfy, Gehad; Said, Mohamed M.; El Ashry, El Sayed H.; El Tamany, El Sayed H.; Soliman, Saied M.; Abu-Serie, Marwa M.; Teleb, Mohamed; Yousuf, Sammer; Dömling, Alexander; Domingo, Luis R.; Barakat, Assem (Frontiers in Chemistry, 2021)
The tumor resistance to p53 activators posed a clinical challenge. Combination studies disclosed that concomitant administration of Bcl2 inhibitors can sensitize the tumor cells and induce apoptosis. In this study, we utilized a rapid synthetic route to synthesize two novel hybrid spirooxindole-based p53-MDM2 inhibitors endowed with Bcl2 signaling attenuation. The adducts mimic the thematic features of the chemically stable potent spiro[3H-indole-3,2′-pyrrolidin]-2(1H)-ones p53-MDM2 inhibitors, while installing a pyrrole ring via a carbonyl spacer inspired by the natural marine or synthetic products that efficiently inhibits Bcl2 family functions. A chemical insight into the two synthesized spirooxindoles including single crystal X-ray diffraction analysis unambiguously confirmed. The synthesized spirooxindoles 2a and 2b were preliminarily tested for cytotoxic activities against normal cells, MDA-MB 231, HepG-2 and Caco-2 via MTT assay. 2b was superior to 5-fluorouracil. Mechanistically, 2b induced apoptosis-dependent anticancer effect (43%) higher than that of 5-fluorouracil (34.95%) in three studied cancer cell lines, activated p53 (47%), downregulated the Bcl2 gene (1.25 folds) and upregulated p21 (2 folds) in the treated cancer cells. Docking simulations declared the possible binding modes of the synthesized compounds with MDM2.